2016
DOI: 10.1016/j.rmb.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-cultured aquatic fungal diversity from different habitats in Mexico

Abstract: With the aim to explore the diversity of aquatic fungi in Mexico we present an investigation using a fragment of the 18S ribosomal DNA as a molecular marker obtained from different water bodies (marine, brackish and fresh water). Ribosomal gene fragments were obtained by DNA amplification, the resulting sequences were compared using multiple alignments against a collection of classified reference fungal sequences and then subjected to phylogenetic clustering allowing the identification and classification of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(42 reference statements)
2
6
0
Order By: Relevance
“…Sordariomycetes also was the most recovered class from aquatic environments from Mexico and the other classes like Saccharomycetes, Eurotiomycetes. Leotiomycetes, Dothideomycetes, Sordariomycetes, Tremellomycetes and Chytridiomycetes also were observed in this study (Valderrama et al 2016). Microbotryomycetes are Basidiomycete yeasts common to aquatic environments like mangroves.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Sordariomycetes also was the most recovered class from aquatic environments from Mexico and the other classes like Saccharomycetes, Eurotiomycetes. Leotiomycetes, Dothideomycetes, Sordariomycetes, Tremellomycetes and Chytridiomycetes also were observed in this study (Valderrama et al 2016). Microbotryomycetes are Basidiomycete yeasts common to aquatic environments like mangroves.…”
Section: Discussionsupporting
confidence: 73%
“…Members of this Phylum generally decompose cellulose selectively over lignin (Osono 2007) and dominate the fungal community and are highly active (production of extracellular enzymes) in the early stages of litter decomposition (Zhang et al 2018). Aquatic ascomycetes play important roles in wood and leaf litter degradation since basidiomycetes are found in lower quantities (Valderrama et al 2016). Ascomycetes appear to be better able to withstand the conditions prevailing in aquatic habitats, far more than basidiomycetes (Jones and Choeyklin 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those were registered in the Pacific ocean. 7 Members of this phylum are zoosporic fungi that use a monocentric thallus as anucleate filamentous rhizoids to anchor the substrate absorb their nutrients. They are saprophytes, pathogens and can degrade chitin, cellulose, and keratin.…”
Section: Resultsmentioning
confidence: 99%
“…1 The studied fungi were isolated from coastal water and foam, sand beach, detritus, mangrove wood, and rhizosphere. [2][3][4][5][6][7][8][9][10][11][12][13] Gonzalez et al, 3 reported the last checklist of marine fungi in México, where it contained sixtyone ascomycetes and one basidiomycete, all of them isolated by culture. Since then, only ten papers on marine fungi in México have been published.…”
Section: Introductionmentioning
confidence: 99%